Basic Scale on Insomnia complaints and Quality of Sleep (BaSIQS): Reliability, initial validity and normative scores in higher education students - Gomes, Ana Allen (2015)
Based on successive samples totaling more than 5000 higher education students, we scrutinized the reliability, structure, initial validity and normative scores of a brief self-report seven-item scale to screen for the continuum of nighttime insomnia complaints/perceived sleep quality, used by our team for more than a decade, henceforth labeled the Basic Scale on Insomnia complaints and Quality of Sleep (BaSIQS). In study/sample 1 (n = 1654), the items were developed based on part of a larger survey on higher education sleep-wake patterns. The test-retest study was conducted in an independent small group (n = 33) with a 2-8 week gap. In study/sample 2 (n = 360), focused mainly on validity, the BaSIQS was completed together with the Pittsburgh Sleep Quality Index (PSQI). In study 3, a large recent sample of students from universities all over the country (n = 2995) answered the BaSIQS items, based on which normative scores were determined, and an additional question on perceived sleep problems in order to further analyze the scale's validity. Regarding reliability, Cronbach alpha coefficients were systematically higher than 0.7, and the test-retest correlation coefficient was greater than 0.8. Structure analyses revealed consistently satisfactory two-factor and single-factor solutions. Concerning validity analyses, BaSIQS scores were significantly correlated with PSQI component scores and overall score (r = 0.652 corresponding to a large association); mean scores were significantly higher in those students classifying themselves as having sleep problems (p < 0.0001, d = 0.99 corresponding to a large effect size). In conclusion, the BaSIQS is very easy to administer, and appears to be a reliable and valid scale in higher education students. It might be a convenient short tool in research and applied settings to rapidly assess sleep quality or screen for insomnia complaints, and it may be easily used in other populations with minor adaptations.